Pollinator sampling methods influence community patterns assessments by capturing species with different traits and at different abundances. (December 2021) - Thompson, Amibeth; Frenzel, Mark; Schweiger, Oliver; Musche, Martin; Groth, Till; Roberts, Stuart P.M.; Kuhlmann, Michael; Knight, Tiffany M.
Highlights: Pollinator communities are compared between two common sampling methods. Sampling methods capture different species richness and composition of pollinators. This results from differences in the abundance and traits of individuals captured. Quantifying sampling effort and functional traits are key for future syntheses. Abstract: In order to synthesize changes in pollinating insect communities across space and time, it is necessary to understand whether, and how, sampling methods influence assessments of community patterns. We compared how two common sampling methods—yellow combined flight traps and net sampling—influence our understanding of the species richness, abundance and composition of wild bees and hoverflies, and addressed whether these patterns resulted from potentially biased sampling of individuals or species with different types of functional traits. We sampled bee and hoverfly communities in six sites over three seasons in Saxony-Anhalt, Germany. We captured more species and individuals of bees with traps and more species and individuals of hoverflies with net sampling. However, rarefied richness results were less dramatic between the sampling methods for bees and were not different between the sampling methods for hoverflies. Thus, differences in species richness across sampling methods were mostly due to differences in the number of individuals captured in the different methods. We captured more small-sized bees and hoverflies with traps. We tested if the different methods collected individuals and species with different functional traits, such as nesting preferences, sociality and flower specialization for bees and floral preference, migratory status and habitat preference for hoverflies. For most traits, we collected more individuals but not more species with a certain trait in the different methods. This was mainly due to a high abundance of one species being collected in the different methods. These results suggest that the best methodology depends on the aim of the survey, and that the methods cannot be easily combined into synthesis research. Our results have implications for the development of monitoring schemes for pollinators and for synthesis of trends that can identify threats to pollinators and inform research of pollinator conservation strategies.